Efektivitas Operasi Gempur Rokok Ilegal di Kota Pekanbaru - Dian Rahma Dani; Dadang Mashur (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Illegal Cigarette Fighting Operation is an organized, coordinated, simultaneous and massive operation or strategy from upstream to downstream to eradicate the circulation of illegal cigarettes. This research aims to describe the effectiveness of the Illegal Cigarette Gempur Operation in Pekanbaru City and to determine the factors inhibiting the effectiveness of the Illegal Cigarette Gempur Operation in Pekanbaru City using Campbell's theory of effectiveness in Mutiarin (2021) which is seen from the aspects of program success, target success, program satisfaction, level input And output and achieving overall goals. This research uses descriptive qualitative methods. The results of this research show that the Operation to Fight Illegal Cigarettes in Pekanbaru City is still not effective. This can be seen from several indicators of effectiveness which show that stalls that have been prosecuted are still selling illegal cigarettes, the Illegal Cigarette Fighting Operation has not been carried out thoroughly in Pekanbaru City so there are still stalls that have not been prosecuted and illegal cigarettes are still circulating as well as awareness or participation. the community in supporting the implementation of Operation Combat Illegal Cigarettes by reporting if there are still minimal finds of illegal cigarettes in their surroundings. The inhibiting factors in the effectiveness of the Illegal Cigarette Fighting Operation in Pekanbaru City are limited Human Resources (HR), resistance from the community, public knowledge and the development of smuggling modes. The suggestion from this research is that there is a need for an educational campaign that touches all levels of society, the imposition of stricter sanctions to provide a deterrent effect and an increase in the frequency of more massive enforcement.